"El Único Problema Aquí": A Cristero Family and Workin Los Angeles, 1927–1932. Issue 2 (31st March 2020) - Stalls, Clay
Abstract: The Venegas family letters at Loyola Marymount University present an unusual opportunity to document the work trajectories of their authors, Dolores Dávalos de Venegas and Miguel Venegas, after their exile to Los Angeles in 1927 because of the Cristero conflict in their home state of Jalisco, Mexico. Like many Mexican migrants to Los Angeles, Miguel began work in a blue-collar job, but within six months he had acquired a modest grocery store in central Los Angeles. Miguel's middle-class business background in Jalisco provided him with the skills, worldview, and probable capital to move into business in Los Angeles.